Therapeutic Hypothermia and the Risk of Hemorrhage: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 47 (November 2015) - Wang, Chih-Hung; Chen, Nai-Chuan; Tsai, Min-Shan; Yu, Ping-Hsun; Wang, An-Yi; Chang, Wei-Tien; Huang, Chien-Hua; Chen, Wen-Jone
Abstract : Abstract: Current guidelines recommend a period of moderate therapeutic hypothermia (TH) for comatose patients after cardiac arrest to improve clinical outcomes. However, in-vitro studies have reported platelet dysfunction, thrombocytopenia, and coagulopathy, results that might discourage clinicians from applying TH in clinical practice. We aimed to quantify the risks of hemorrhage observed in clinical studies. Medline and Embase were searched from inception to October 2015. Randomized controlled trials (RCTs) comparing patients undergoing TH with controls were selected, irrespective of the indications for TH. There were no restrictions for language, population, or publication year. Data on study characteristics, which included patients, details of intervention, and outcome measures, were extracted. Forty-three trials that included 7528 patients were identified from 2692 potentially relevant references. Any hemorrhage was designated as the primary outcome and was reported in 28 studies. The pooled results showed no significant increase in hemorrhage risk associated with TH (risk difference [RD] 0.005; 95% confidence interval [CI] −0.001–0.011; I 2, 0%). Among secondary outcomes, patients undergoing TH were found to have increased risk of thrombocytopenia (RD 0.109; 95% CI 0.038–0.179; I 2 57.3%) and transfusion requirements (RD 0.021; 95% CI 0.003–0.040; I 2 0%). The meta-regression analysis indicated that prolonged duration of cooling may be associated with increased risk of hemorrhage. TH was not associated with increased risk of hemorrhage despite the increased risk of thrombocytopenia and transfusion requirements. Clinicians should cautiously assess each patient's risk-benefit profile before applying TH. Abstract : Supplemental Digital Content is available in the text